PEMANFAATAN TEKNOLOGI INFORMASI DALAM PENGEMBANGAN SISTEM INFORMASI DESA DAN DIGITALISASI UMKM SERUNDENG DI DESA JAGAPATI - I Putu Eka Indrawan; Ni Luh Gde Widiantari; Luh De Surya Augustine Maharani; I Dewa Gede Satya Cakra Dharma; I Komang Adhi Putra; A.A Putu Cinthya Sandra Wulandari; Putu Ananta Krsna Maharana; I Kadek Wirya Udiana; I Kadek Suta Puspanjaya; I Wayan Gede Indra Purnayasa; A.A Bagus Eka Pratama; I komang Risky Sastrawan; I Komang Putrayasa; Agustina Kurniati; Rikardus wagung (Sewagati, 2025)
The community service program conducted by Group 9 of Universitas PGRI Mahadewa Indonesia aimed to utilize information technology to support digital transformation in Jagapati Village, Abiansemal District, Badung Regency. The team designed and implemented a web-based village information system to improve the efficiency of public services and accelerate community access to population data, traditional activities, and official announcements. In addition, the team assisted local serundeng (fried coconut condiment) MSMEs in the digitization of their businesses through training in digital product catalog creation, modern packaging design, and QR code integration as a digital marketing tool. The implementation methods included initial observation, participatory planning, direct execution, and evaluation based on community feedback. The results showed that the village information system helped local authorities manage data more systematically and transparently, while the digitization of MSMEs increased the competitiveness of local products and expanded market opportunities. This program demonstrates that collaboration between university students, village officials, and the local community can foster digital independence and culture-based economic empowerment. Through a contextual and solution-oriented approach, the initiative has contributed meaningfully to building a smart village that is technologically adaptive while remaining rooted in traditional values